ChemInform Abstract: Structural Properties and Charge Distribution of the Sodium Uranium, Neptunium, and Plutonium Ternary Oxides: A Combined X‐Ray Diffraction and XANES Study. Issue 16 (March 2016) - Smith, Anna L.; Martin, Philippe; Prieur, Damien; Scheinost, Andreas C.; Raison, Philippe E.; Cheetham, Anthony K.; Konings, Rudy J. M.
Abstract: In the frame of a potential contact of MOX fuels with the Na coolant in fast breeder reactors, the chemistry and charge distributions in α‐Na2 UO4, Na3 NpO4, α‐Na2 NpO4, Na4 NpO5, Na5 NpO6, Na2 PuO3, Na4 PuO5, and Na5 PuO6 are investigated by XANES spectroscopy at the U‐L3, Np‐L3, and Pu‐L3 edges.